ANALYSIS OF THE RELATIONSHIP BETWEEN ENVIRONMENTAL PERFORMANCE AND ENVIRONMENTAL DISCLOSURE IN LIGHT OF THE SUSTAINABLE DEVELOPMENT GOALS - Mota, Joaes dos Santos Oliveira; Pimentel, Márcio Sampaio (Advances in Scientific and Applied Accounting, 2022)
Objective: This study aimed to analyze the relationship between corporate environmental performance and corporate environmental disclosures of companies listed on B3 that released their sustainability reports, considering the Sustainable Development Goals concerning the environmental dimension. Method: The methodology is basic, descriptive, explanatory and documentary, and concerning the approach, quantitive, census type, with a total of 61 sustainability reports evaluated. In line with the objective of this study and in order to analyze the results, we chose to use the Multiple Linear Regression Analysis. Results or Discussion: The findings showed that environmental performance has a positive (moderate to strong) and significant (p-0.01) relationship with environmental disclosure, explaining 43% of the disclosure of environmental information by companies in the studied universe. Another model variable, the nature of the activity, can also be associated with environmental disclosure, explaining 4.9%. These results are consistent with what the Theory of Legitimacy predicted, reinforcing that companies’ strategies, reflected in their environmental performance, can explain the levels of their environmental disclosure. Contributions: It is believed that it will provide an in-depth diagnosis of the relationship between the degree of environmental performance and the extent of environmental disclosure during the period, verifying and quantifying it.